The Prophet’s Da’wah to Jews & their Opposition (A research-based study on its causes and reasons) - Riyaz, Muhammad; Aslam Rao, Dr. Muhammad Atif (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Before the migration of the Holy Prophet ﷺ, Madinah was inhabited by Jews. They possessed some of the most fertile lands in Madinah and carried on several crafts, especially as goldsmiths. The Jews acted as moneylenders to the Arabs. They had many strongholds in and around Madinah. Thus, the Jews had a firm position in Madinah. The Holy Prophet ﷺ, irrespective of Jewish attitude, tried his level best to maintain a friendly relationship with the Jews. They were granted political, social and religious freedom. However, the Jews became increasingly hostile to the Muslims despite these rights and concessions as they wanted to dominate Arabia politically and religiously. Thus, they expressed their bitterness and hostility in many ways, which worsened their relations with the Muslims. This research is aimed at highlighting the history, socio-political status and conspiracies of Jews. The researcher presented detailed accounts on the opponent and rigid behaviour of Jews along with their character. The distinct element of the article is the references and a discourse on the Jewish tribes who opposed Islam openly. The researcher also worked out the causes why a call to Islam for Jews was indispensable. Likewise, he also mentioned the reasons and the causes of opposition from the then Jews. Jews, out of jealousy did not accept Islam. However, they kept demanding multiple things as previous. The article also mentions them. This piece of research is highly recommended for the young generation who are unaware of the history and attitude of the Jews that continued since the times of the Prophets.